1997
DOI: 10.1046/j.1423-0410.1997.7220093.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Intravenous and Subcutaneous Recombinant Human Erythropoietin (Epoetin Alfa) Administration in Presurgical Autologous Blood Donation in Anemic Rheumatoid Arthritis Patients Undergoing Major Orthopedic Surgery

Abstract: Lower dose of Epoetin alfa (reduced by 56%), supplemented by i.v. iron, is as effective and well tolerated as higher doses administered i.v., supplemented by i.v. iron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This assay has a sensitivity (95% detection rate) of ∼7.3 IU/ml (approximately 29 genome equivalents/ml) [4], corresponding to a sensitivity of 700 IU/ml for any reactive donation contained in the origined pool. We performed retesting and subsequent resolution to individual donation levels of any pools confirmed reactive by testing 20 sub–pools (12 and 8 donations) [5]. …”
Section: Introductionmentioning
confidence: 99%
“…This assay has a sensitivity (95% detection rate) of ∼7.3 IU/ml (approximately 29 genome equivalents/ml) [4], corresponding to a sensitivity of 700 IU/ml for any reactive donation contained in the origined pool. We performed retesting and subsequent resolution to individual donation levels of any pools confirmed reactive by testing 20 sub–pools (12 and 8 donations) [5]. …”
Section: Introductionmentioning
confidence: 99%
“…The optimization of the route of administration of r–HuEPO to reduce the dosage and consequently the cost of this therapy was addressed in previous trials. It was demonstrated that subcutaneous administration of r–HuEPO was more effective that the intravenous route, allowing reduction of both dose and frequency of injection needed for preoperative storage of autologous blood [20, 21, 22, 23, 24]. In fact, serum erythropoietin levels remained elevated for 36–48 h after r–HuEPO subcutaneous administration compared to few hours after intravenous infusion [23].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in patients with rheumatoid arthritis scheduled for major orthopaedic surgery, the presence of a low pre-donation haematocrit (Hct < or = 39%) can preclude the donation of sufficient autologous blood to meet transfusion requirements. The use of rHuEPO, in conjunction with IV iron supplementation to maximize its beneficial effects, has shown to be well tolerated and facilitates preoperative autologous blood donation and reduces exposure to allogeneic blood in this patient population [24].…”
Section: Elective Surgerymentioning
confidence: 99%